2013
DOI: 10.1523/jneurosci.5555-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Activity-Independent Turnover of Vesicular Transmitter Content at a Mixed Glycine/GABA Synapse

Abstract: The release of neurotransmitter via the fusion of transmitter-filled, presynaptic vesicles is the primary means by which neurons relay information. However, little is known regarding the molecular mechanisms that supply neurotransmitter destined for vesicle filling, the endogenous transmitter concentrations inside presynaptic nerve terminals or the dynamics of vesicle refilling after exocytosis. We addressed these issues by recording from synaptically-coupled pairs of glycine/GABA co-releasing interneurons (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 66 publications
(121 reference statements)
2
96
1
Order By: Relevance
“…In support of this view, a study of peripheral cholinergic synapses indicated that inhibition of the vesicular ACh transporter did not reduce vesicular content in the absence of stimulation (42). In contrast, at glycine/GABA coreleasing interneuron varicosities, the vesicular GABA content is depleted by blocking cytosolic GABA synthesis, independent of exocytosis (43). This leaky nature of GABA through the lipid bilayer was also shown in proteoliposomes (10).…”
Section: Discussionmentioning
confidence: 91%
“…In support of this view, a study of peripheral cholinergic synapses indicated that inhibition of the vesicular ACh transporter did not reduce vesicular content in the absence of stimulation (42). In contrast, at glycine/GABA coreleasing interneuron varicosities, the vesicular GABA content is depleted by blocking cytosolic GABA synthesis, independent of exocytosis (43). This leaky nature of GABA through the lipid bilayer was also shown in proteoliposomes (10).…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, in vivo work has suggested that GABAergic inhibition also controls the response properties of cartwheel and fusiform cells (Davis and Young 2000), and a recent in vitro study suggested that GABAergic inhibition controls the spread of parallel fiber excitation in the DCN (Middleton et al 2011). Since cartwheel cell transmission is predominantly glycinergic (Apostolides and Trussell 2013a;Golding and Oertel 1997;Mancilla and Manis 2009;Roberts et al 2008), these results suggest that stellate cells are a likely source of GABAergic inhibition.…”
mentioning
confidence: 94%
“…The neuronal GlyT2 transporter is involved in the removal and recycling of glycine from inhibitory synapses, generating a flux from the synaptic cleft to the presynaptic terminal and supplying substrate to the low affinity vesicular inhibitory amino acid transporter (2,3). Therefore, the synaptic glycine taken up by GlyT2 is the main source of the releasable transmitter at glycinergic synapses (4,5). Accordingly, inactivation of the mouse GlyT2 gene generates a complex postnatal neuromotor phenotype that mimics clinical signs of human hyperekplexia (2).…”
mentioning
confidence: 99%